Community Care Service Dalam Penanganan Lansia Terlantar Di Kabupaten Gorontalo Utara - Arsyad, Yolandika; Suleman, Syahputra Adisanjaya; Rahmawati, Rahmawati (Jurnal Publisitas, 2025)
Elderly individuals, defined as those aged over 60, are a vulnerable population within society. They are particularly susceptible to neglect due to declining physical and social functions, leading close family members to perceive them as burdens. Consequently, social services for the elderly are categorized into institutional and non-institutional care. The concept of community care is a form of non-institutional social service that involves community participation in addressing the issues faced by the elderly. This study aims to analyze the activities of the "LKS Orang Tua Asuh" in addressing the problem of neglected elderly individuals in North Gorontalo Regency, using the community care concept as a framework. A qualitative method with in-depth interview techniques was employed in this research. The findings reveal that the activities conducted by "LKS Orang Tua Asuh" align with a community development-based approach. These activities share key characteristics, including tailoring programs to community needs, involving staff in planning and implementation, gathering information about community needs through local engagement, and evaluating program success based on feedback from beneficiaries and the broader community. This approach has successfully mobilized community members to assist in solving the issues faced by neglected elderly individuals in North Gorontalo Regency.